Examining Ecological Footprints in the backdrop of Institutional Quality, Economic Growth, FDI and Urbanisation - Sharmiladevi, J. C. (International Journal of Energy Economics and Policy, 2025)
The objective of this study is to identify the impact of economic growth, international trade, cross-border capital movement, institutional quality and urbanisation upon the ecological footprints for the case of India for the period from 2000 to 2024. After checking the data for unit roots and ensuring data stability, the ARDL model was calculated, with bounds test and error correction. The model is able to explain 66.8 per cent of the total changes, bounds test results indicate long-term equilibrium relations among the variables. Error correction term satisfies stability, showing a negative and significant coefficient score of -1.20 rate of returning to equilibrium. Stability and diagnostic tests, recursive estimates indicate significant results. Impulse response function results show an asymmetrical relation with all the dependent variables. Inclusion of institutional quality adds uniqueness to this study, and this paper bridges the gap in identifying the role of institutional factors in impacting ecology considering economic factors and environmental challenges